Pemahaman Politik dan Identifikasi Kepartaian Generasi Muda serta Implikasinya terhadap Perilaku Memilih - Suryanef, Suryanef (Pusat Kajian Civics Fakultas Ilmu-ilmu Sosial Universitas Negeri Padang, 2002)
This research aims to describe the factors which influence the voting behavior of young generation in general election 1999 in Padang Timur, West Sumatra. There are two clarifies variables that are used. They are : political comprehension and party identification. While the problems of this research are: Fisrtly, how much significance of political comprehension and party identification influence the voting behavior of young generation? Secondly, in all of that determine factors, which one is the most influence toward the voting behavior of young generation? Questionaires were distributed to 96 respondents in five kelurahan in Kecamatan Padang Timur. The data was analyzed by multi-regression methods. The result of analysis shows that there is a significance influence from political comprehension and party identification simultaneously toward the voting behavior. These two variables can give explanation about the voting behavior 54,48%, where as the biggest contribution is given by political comprehension about 68,16%. Key Words: Pemahaman Politik, Identifikasi Kepartaian, Perilaku Memilih